ANALISIS NILAI KARAKTER NASIONALISME PADA KESENIAN JARANAN TURONGGO MUDO NGESTI BUDOYO DI DESA MARGA MULYA, KECAMATAN SUNGAI BAHAR, KABUPATEN MUARO JAMBI - Apriliana; Tohap Pandapotan Simaremare; Sundari Utami (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is motivated by the decline in member participation in the Jaranan Turonggo Mudo Ngesti Budoyo art form in Marga Mulya Village, where the number of inactive members reached 51%, surpassing the 49% of active members. This phenomenon threatens the continuity of the art form and hinders the embedding of nationalism values contained within it. The research employs a qualitative descriptive approach, using data collection techniques such as observation, interviews, and documentation. Data analysis was conducted through the stages of data collection, presentation, reduction, and drawing conclusions. The results of the study show that the Jaranan Turonggo Mudo Ngesti Budoyo art form embodies nationalism values reflected in various aspects. Religious aspects are evident through prayers before and after performances. The preservation of the Javanese language and local culture through songs and communication represents a tangible expression of love for one’s own culture. Attitudes of tolerance and respect for diversity are also demonstrated by the use of both Javanese and Indonesian languages interchangeably, as well as openness to ethnic and religious differences. Furthermore, this art form maintains its cultural identity through distinctive elements such as dance and horse props, while actively ensuring regeneration to guarantee its sustainability. Jaranan art has proven to be an effective medium for instilling nationalism values, such as patriotism, respect for culture, and pride in local identity. Therefore, support for the existence and development of this art form is crucial to keep it as part of the formation of Indonesia's national character and identity.